Experimental Investigation of the Heat Flux Distribution in Grinding of Titanium Alloy. (2015) - Fritsche, A.; Bleicher, F.
Abstract: Generally, grinding involves high specific energy, compared to other machining processes. Most of this energy is changed into heat which makes harmful effects on surface quality as well as tool wear. In this respect temperature measurement techniques enhance cutting performance in terms of increasing wheel life and improving the quality of the ground part, especially when grinding temperature sensitive material like γ-TiAl. The distribution of the total grinding heat flux along the grinding zone does not follow a linear form. It increases at the trailing edge with sharp gradients and then varies nearls linearly for the renaibder of the contact length. In this paper a new method to measure relative temperature in the grinding zone is presented. The approach demonstrates a flexible arrangement of the thermocouple in the workpiece to measure at variable depth of cuts. The results of the experiments are further investigated to cover the mentioned complex distribution of the heat flux in the workpiece. With the known relative temperature in the grinding zone and the net spindle power is a simple analytical approach presented to estimate the absolute grinding temperature. It is shown that the measured and the calculated temperature diver up to 600%.